ANALISIS PENGGUNAAN LAGU SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN PEMAHAMAN MATERI PADA SISWA KELAS VI SD NEGERI PURWOKERTO 01 KECAMATAN TAYU - Asriani, Wulan; Eka Titi Andaryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning media is one of the important things in classroom learning. Because this can determine the activeness and understanding of the material in students. However, conventional methods that are often used are considered less interesting for students and cause low student involvement in learning and understanding the material. This study aims to analyze the use of song-based learning media in improving students' understanding of learning materials. This research method is a qualitative method. Data collection techniques use interviews, documentation, and observation. The data analysis technique used is qualitative descriptive. The results of this study show that: 1) The application of innovative media of songs is effective in increasing students' understanding of learning materials. 2) Careful learning planning is the key to success in the application of song media in learning. 3) Supporting factors such as support from the school, teacher creativity, and student enthusiasm play an important role in learning. 4) There are several obstacles in the application of song media such as time limitations, differences in student learning styles, and lack of teacher training.